On dynamics of a class of ξ(s) quadratic stochastic operators on 2D simplex - Mukhamedov, Farrukh; Saburov, Mansoor; Qaralleh, Izzat (2012)
In this paper, we are going to study the dynamics of ξ(s)-quadratic stochastic operators (in short QSO) which appeared from the partition with two elements. We are also going to study the trajectory of one class of operators from the derived classes.